The Role of Digital Technology within the Business Model of Sustainable Entrepreneurship - Fuerst Sascha; Sanchez-Dominguez Odille; Rodriguez-Montes Miguel Angel (MDPI, 2025)
The adoption and usage of digital technologies is considered one of the most promising transformations for sustainability, and sustainable entrepreneurship is considered key for providing solutions for the grand social and environmental challenges. The purpose of our study is to shed light on the role of digital technologies in value creation, value delivery, and value capture within the business models of sustainable entrepreneurship. This is important for understanding how digital technologies leverage sustainability. In fact, we have little knowledge on the impact of digital technologies within the business models of sustainable entrepreneurship. We studied the adoption and usage of digital technologies within the business models of 10 born-sustainable new ventures in Mexico applying a comparative case study approach. We found that context matters. Extant research claims that digital technologies promote social inclusion, increase connectivity, and lead to broader stakeholder integration. Despite these claims, this is the most challenging part for entrepreneurs. Our main findings, therefore, emphasize the constraints of the implementation of digital technologies within sustainable business models. This adds to the academic discourse a cross-geographic perspective from the Global South.